2020
DOI: 10.1101/2020.08.07.241695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Historical genomics reveals the evolutionary mechanisms behind multiple outbreaks of the host-specific coffee wilt pathogen Fusarium xylarioides

Abstract: 1AbstractNearly 50% of crop yields are lost to pests and disease, with plants and pathogens locked in an amplified co-evolutionary process of disease outbreaks. Coffee wilt disease, caused by Fusarium xylarioides, decimated coffee production in west and central Africa following an initial 1920s outbreak. After successful management, it later re-emerged reaching two separate epidemics by the 2000s on arabica coffee in Ethiopia and robusta coffee in east and central Africa. Here, we use genome sequencing of six … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 80 publications
(109 reference statements)
1
2
0
Order By: Relevance
“…The results presented here are also consistent with studies showing that RIP is acquired in an isolate-specific manner [8,69,70]. A recent study of Fusarium xylarioides (a close relative of F. circinatum) reported RIP-driven diversification were more prevalent amongst putative effector genes than for any other type of gene classification [71]. Together these data suggest that RIP is an important source of variation in gene regions underlying important biological traits, pathogen development and host-pathogen interactions in F. circinatum and other fungi.…”
Section: Discussionsupporting
confidence: 91%
“…The results presented here are also consistent with studies showing that RIP is acquired in an isolate-specific manner [8,69,70]. A recent study of Fusarium xylarioides (a close relative of F. circinatum) reported RIP-driven diversification were more prevalent amongst putative effector genes than for any other type of gene classification [71]. Together these data suggest that RIP is an important source of variation in gene regions underlying important biological traits, pathogen development and host-pathogen interactions in F. circinatum and other fungi.…”
Section: Discussionsupporting
confidence: 91%
“…tritici , the loss of the AvrSr27 locus that is recognized by the major Sr27 resistance locus in wheat was found to arise independently in multiple field strains that became virulent on wheat cultivars carrying Sr27 resistance (Upadhyaya et al ., 2021). Gains of effectors* through horizontal gene transfer* underlie specialization on new hosts in the wheat pathogens Parastagonospora nodorum , Pyrenophora tritici‐repentis and Bipolaris sorokiniana (McDonald et al ., 2019), and in host‐specialized Fusarium species (Peck et al ., 2021). One intriguing trend that has been identified repeatedly is the higher proportion of gene gains and losses in fungal plant pathogens from agricultural ecosystems than in fungal plant pathogens from forest or wild ecosystems.…”
Section: Multiple Eco‐evolutionary Processes In Fungal Plant Pathogen...mentioning
confidence: 99%
“…Structural variants often are particularly abundant near centromeres (Carpentier et al ., 2019; Seidl et al ., 2020), regions with a high repeat content (Faino et al ., 2016; Badet et al ., 2021; Peck et al ., 2021; Torres et al ., 2021) or regions with epigenetic marks contrasting with other regions of the genome, such as heterochromatin (Cook et al ., 2020; Soyer et al ., 2021). Likewise, although the mechanisms of horizontal gene transfer* in eukaryotes remain poorly understood, a genome‐wide survey of horizontal gene transfer* events in V. dahliae showed that such events occur preferentially in repeat‐rich regions of the genome (Shi‐Kunne et al ., 2019).…”
Section: Promising Avenues Of Research Using Structural Variants In F...mentioning
confidence: 99%